Use the Commutative Property to determine the missing step in proving the equivalence of 12a+10+a=10+a+12a . Step 1: [missing] Step 2: 10+13a=10+13a Step 3: The expressions are equivalent because they both equal the same value. (1 point) Responses 12a+10+a−a=10+a+12a−a d plus 10 plus a equals 10 plus a plus d 12a+10=10+12a d plus 10 plus a equals 10 plus a plus d 10+12a+a=10+13a d plus 10 plus a equals 10 plus a plus d 12a+10+a−10=10+a+12a−10

3 answers

To determine the missing step using the Commutative Property, we need to recognize that the Commutative Property allows us to rearrange the terms in an expression without changing its value.

Given the expression on the left side: \[12a + 10 + a\]

We can combine the like terms (12a + a), which gives us: \[ (12a + a) + 10 = 13a + 10\]

However, since we are looking for a way to rearrange the terms from \( 12a + 10 + a \) to the form given in Step 2, we should focus on rearranging the initial expression accordingly.

The missing step involves rearranging the terms using the Commutative Property. The expression can be rearranged like this:

Step 1: \( 10 + a + 12a = 10 + a + 12a \)

So the correct response is: 10 + 12a + a = 10 + a + 12a

This leads directly to Step 2 as intended.

which answer is it?

The correct answer for the missing step is:

10 + 12a + a = 10 + a + 12a

This step effectively uses the Commutative Property to rearrange the terms.